Metastatic salivary gland carcinoma: A role for stereotactic body radiation therapy? A study of AIRO‐Head and Neck working group. (25th December 2020) - Franzese, Ciro; Ingargiola, Rossana; Tomatis, Stefano; Iacovelli, Nicola Alessandro; Beltramo, Giancarlo; Franco, Pierfrancesco; Bonomo, Pierluigi; Zanetti, Isa Bossi; Argenone, Angela; Cante, Domenico; Romanello, Domenico Attilio; Musio, Daniela; et al.
Abstract: Objectives: The role of radiotherapy (RT) for oligometastases is currently established in different oncological settings but data on salivary gland cancer (SGC) are lacking. We evaluated the role of RT in oligometastatic SGC patients, focusing on stereotactic body radiation therapy (SBRT). Materials and methods: We performed a retrospective, multicentric study of oligometastatic SGC treated with palliative RT or SBRT. Endpoints included response evaluation and local control (LC). Results: Between 2006 and 2016, 64 patients were collected from 9 Italian Cancer Centers, on behalf of the Italian Association of Radiotherapy and Clinical Oncology (AIRO) Head and Neck Working Group. 37 patients (57.8%) were suffering from adenoid cystic carcinoma (ACC) and 27 patients (42.2%) had non‐ACC. Thirty‐four patients underwent palliative RT (53, 1%), and 30 received SBRT (46, 9%). Most common metastatic sites were bone for palliative RT and lung for SBRT. Among patients treated with SBRT, an objective response or a stability was observed in all treated lesions. After a median follow‐up of 29.2 months (range 2.3–117.1), LC at 12 months was 57.5% for patients treated with SBRT and was higher in ACC subgroup. Conclusion: We confirmed the potential role of SBRT in the management of oligometastatic SGC patients to control limited burden of disease considering the absence of effective systemic therapies.